Some Ideas About Resource Centers - Edmundo Mora (Asociación Colombiana de Profesores de Ingles, 2016)
The constant advancement of technology and science is a worldwide fact. Teachers who work at various educational levels cannot ignore this reality. Linguistics is not an exception to this rule. For instance, during the 50's and early 60's, psycholinguistics theory was influenced basically by behavioristic theory from such psychologists as Skinner and by Structural Linguistics of taxonomic structuralists such as Bloomfield.